Prevalence of Seizures in Pediatric Extracorporeal Membrane Oxygenation Patients as Measured by Continuous Electroencephalography. Issue 12 (December 2018) - Okochi, Shunpei; Shakoor, Aqsa; Barton, Sunjay; Zenilman, Ariela R.; Street, Cherease; Streltsova, Svetlana; Cheung, Eva W.; Middlesworth, William; Bain, Jennifer M.
Abstract : Objectives: Standards for neuromonitoring during extracorporeal membrane oxygenation support do not currently exist, and there is wide variability in practice. We present our institutional experience at an academic children's hospital since establishment of a continuous electroencephalography monitoring protocol for extracorporeal membrane oxygenation patients. Design: Retrospective, single-center study. Setting: Neonatal ICU and PICU in an urban, quaternary care center. Patients: All neonatal and pediatric patients requiring extracorporeal membrane oxygenation. Interventions: None. Measurements and Main Results: During the study period, 70 patients were cannulated for extracorporeal membrane oxygenation and had continuous electroencephalography monitoring for greater than 24 hours. Electroencephalographic seizures were observed in 16 of 70 patients (23%), including five patients (7%) who were in status epilepticus. Among patients with continuous electroencephalography seizures, nine (56%) had subclinical nonconvulsive status epilepticus and eight (50%) had seizures in the initial 24 hours of extracorporeal membrane oxygenation support. Survival to hospital discharge was significantly greater for extracorporeal membrane oxygenation patients without seizures (74% vs 44%; p = 0.02). Conclusions: Seizures occur in a significant proportion of pediatric and neonatal extracorporeal membrane oxygenation patients, frequently in the initial 24 hours after extracorporeal membrane oxygenation cannulation. Because seizures are associated with significantly decreased survival, neuromonitoring early in the extracorporeal membrane oxygenation course is important and useful. Further studies are needed to correlate electroencephalography findings with neurologic outcome. Abstract : Supplemental Digital Content is available in the text.